DETERMINAN YANG MEMPENGARUHI PENGGUNAAN E-FILING MELALUI PEMAHAMAN INTERNET SEBAGAI VARIABEL PEMODERASI : DETERMINANTS THAT INFLUENCE THE USE OF E-FILING THROUGH INTERNET UNDERSTANDING AS A MODERATING VARIABLE - Nada Aristia Maharani; Achmad Badjuri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The purpose of this research was to test and analyze the effect of perceived ease, perceived satisfaction, and perceived benefit on e-Filing use, as well as to determine the effect of internet understanding as a moderating variable that can affect perceived ease, satisfaction, and benefit on e-Filing use. Individual taxpayers registered at KPP Pratama West Semarang were used in this study, totaling 43,948 taxpayers. With a sample size of 100 respondents, the sampling approach employed was simple random sampling. MRA (moderated regression analysis) was employed as the analysis approach. The results explain that perceived ease has a positive effect on the use of e-Filing and perceived benefit has a positive effect on the use of e-Filing, while perceived satisfaction has no significant effect on the use of e-Filing. Meanwhile, internet understanding is able to moderate the effect of perceived ease and perceived benefit on e-Filing use, but internet understanding is not able to moderate the effect of perceived satisfaction on e-Filing use.